Don't Keep It (Too) Simple: How Textual Representations of Scientific Uncertainty Affect Laypersons' Attitudes. (June 2015) - Winter, Stephan; Krämer, Nicole C.; Rösner, Leonie; Neubaum, German
This research investigated the question of how laypersons are influenced by textual representations of scientific uncertainty. In an online experiment ( N = 78), a blog article about effects of computer games on children was presented in four different versions. Each version contained three arguments on negative effects that were either phrased neutrally, contained assertive statements, or included hedges. The fourth version contained an additional argument on positive effects of computer games (two-sided). In comparison with the basic one-sided version, the two-sided text led to a more moderate attitude toward the topic. According to moderation analyses, this difference was mainly based on readers with more advanced epistemological beliefs and with a higher need for cognition, who were more strongly affected by a two-sided presentation of evidence. The assertive version was less effective than the basic version, suggesting that recipients were skeptical when statements were presented as overly certain.